Disputes in Engineering - 'New Propellor', 1941 (1941)
1941 1939-1945 "Disputes in Engineering - 'New Propellor', 1941" [HFR0078], 1941 The front page of New Propellor for 15 February, 1941 carries an article criticising the Essential Works Order 1941, described as 'industrial conscription', and reports of industrial disputes. It also reports the imprisonment of John Mason, a shop steward and Secretary of Mexborough Trades Council, under Defence Regulation 18B, which gave the Home Secretary the right to imprison without trial anybody he believed likely to "endanger the safety of the realm". The first arrests made were of Oswald Mosley and other members of the British Union of Fascists. Mason was accused of "actively obstructing measures to increase production". Despite protests from the Executive Council of the Amalgamated Engineering Union, Mason was detained July 1940 - June 1941.